ACHIEVEMENTS OF HIGHER EDUCATION SYSTEM IN GREATER EAST ASIA - S. I. Lunev (Сравнительная политика, 2016)
The article discusses the importance of higher education institutions in the forming and development of scientific knowledge in the big emerging powers of Asia. It is noted that recently, thepositions of the leading Asian universities have become very much stronger (it is confi rmed by the world rating) due to the radical education reforms (trajectories were very close to each other) that were carried out by the countries of Greater East Asia during the last 25 years. The special programs on the comprehensive development of education were accepted, and its funding was perceived not just as a necessary public expenditure, but as investments to provide the economy with a highly skilled workforce and well-educated professionals. The drastic changes in models of education management are of particular signifi cance. The autonomy of educational institutions can be very high on local level. It is necessary to point out the private sector, which has a crucial signifi cance for Taiwan, South Korea, Japan and China. Exactly universities began playing a major role in scientifi c research in these states. International cooperation in the fi eld of education is also of great importance as it particularly promotes the formation of a cluster of people interested in the development of their own country in an international context.